Between the fragility of life and the insistence of the world - Skliar, Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This text attempts to address the relations between knowledge, world and life and their relationship with education. The problem of knowing is posed in terms of a contradiction between knowing and learning, it seeks in the narration of experience its most finished expression and distinguishes the notions of position and exposure. To this end, the distinction between being and being is taken as a starting point, or, to put it another way, with the forms of being-being that escape identification or conversion into recognizable forms of human existence.